2015
DOI: 10.1089/ten.tea.2015.0019
|View full text |Cite
|
Sign up to set email alerts
|

Positively Charged Oligo[Poly(Ethylene Glycol) Fumarate] Scaffold Implantation Results in a Permissive Lesion Environment after Spinal Cord Injury in Rat

Abstract: Positively charged oligo[poly(ethylene glycol) fumarate] (OPF+) scaffolds loaded with Schwann cells bridge spinal cord injury (SCI) lesions and support axonal regeneration in rat. The regeneration achieved is not sufficient for inducing functional recovery. Attempts to increase regeneration would benefit from understanding the effects of the scaffold and transplanted cells on lesion environment. We conducted morphometric and stereological analysis of lesions in rats implanted with OPF+ scaffolds with or withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 76 publications
2
69
0
Order By: Relevance
“…The extracellular matrix of the injury site lacks guidance cues to promote cell survival and axon outgrowth through an injury field that contains inhibitory molecular cues. Polymer scaffolds may reduce these barriers and provide a multimodal approach to bridge the gap and approximate viable tissue with structured order (Madigan et al, ; Hakim et al, ). They serve as a matrix to guide axonal growth through the area of injury.…”
Section: Introductionmentioning
confidence: 99%
“…The extracellular matrix of the injury site lacks guidance cues to promote cell survival and axon outgrowth through an injury field that contains inhibitory molecular cues. Polymer scaffolds may reduce these barriers and provide a multimodal approach to bridge the gap and approximate viable tissue with structured order (Madigan et al, ; Hakim et al, ). They serve as a matrix to guide axonal growth through the area of injury.…”
Section: Introductionmentioning
confidence: 99%
“…This is most likely to be due to their effect on cell morphology, which has been shown to directly influence osteogenic versus adipogenic differentiation . Producing scaffolds that significantly enhance differentiation toward one lineage whilst inhibiting that toward others could prevent failure of generated tissue due to fibrosis, unwanted fatty tissue formation or ossification …”
Section: Discussionmentioning
confidence: 99%
“…Besides the absence of spontaneous recovery in untreated animals, some authors failed to observe functional motor recovery in injured rodents treated with scaffold-based strategy. 28,36,37 In all abovementioned studies a segment resection model was utilized. It was suggested that the absence of recovery of hindlimbs function in animals subjected to complete spinal cord transection was likely due to insufficient axon regeneration and integration in functional circuit.…”
Section: Discussionmentioning
confidence: 99%